Pelatihan Peningkatan Manajemen Keuangan Dan Digital Marketing Pada UMKM Tape Cipta Rasa Jember - Kurniawati, Dewi; Dhamayanthi, Wenny; Anggraeni, Oktanita Jaya; Sundari, Sri; Ismail, Andi Muhammad (P3M Politeknik Negeri Jember, 2025)
UMKM Tape Brand Cipta Rasa was established in 2010. In financial management, it has not been done properly and does not have a label on its cassava tape product. Seeing this, it is necessary to provide Financial Management and Digital Marketing training so that it can increase the sales volume of this Cipta Rasa brand tape. This method is carried out in 4 stages; survey, provision of materials, practice and tutorials and post-training monitoring. The results of financial training for this partner are that UMKM Tape Brand Cipta Rasa has been able to make financial reports in January and February 2025 and this business has a label on this UMKM Tape Cipta Rasa product business. It is hoped that this UMKM will continue to report financial records in its business so that it can be used in activities, especially for submitting business capital.